100 things not worth repeating : on repetition - Holm Hansen, Marianne ([s.l.] : LemonMelon, 2011)
100 things not worth repeating: on repetition is the result of the survey and subsequent discussions. It presents 100 selected responses* to the survey alongside essays, texts and artworks that employs, explores and considers Repetition from within diverse disciplines; including contributions from David Berridge, Marina Grznic, Rupert Hartley, Juliet Haysom, Roni Horn, Barbara Johnstone, Joan Jonas, James Morris, Jonathan Ree, Fred Scharmen, Mike Solomon, Sue Tompkins, Jill Townsley and Lucy Wilson.
boek